Model dan Gaya Komunikasi dalam Program Upaya Khusus Padi Jagung Kedelai - Nurlaili Nurlaili; Andi Warnaen; Bambang Riyanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2019)
The aim of this research was to examine the model and the style of communication used in the Special Effort Program for Increasing Paddy, Corn and Soybean Production (UPSUS PAJALE). This research was conducted in Tulungagung Regency, East Java Province. This research was a descriptive qualitative research. The research strategy used was a case study. Data collection techniques used in this study were: (1) Observation, (2) In-depth interview, (3) Reviewing documents and archives, and (4) Data collection with Focus Group Discussion (FGD) as a support. The communication model used in UPSUS program in Tulungagung District was a communication model of chain structure in the form of coordinative and linear relationship. UPSUS program communication model in Tulungagung Regency was considered not effective in UPSUS program delivery so there was still a lot of miscommunication at the implementation level below between extension worker with Babinsa and Extension Worker with Mantri Tani. This was because there is no cross-sector coordination and was caused by the controlling style of the stakeholders because of pressure from their superiors, which in the end the interactive communication or effective participatory communication didn't occur.